2004
DOI: 10.1530/eje.0.1500339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucocorticoids on adiponectin: a study in healthy subjects and in Cushing's syndrome

Abstract: Objective: Glucocorticoids were found to inhibit adiponectin gene expression and secretion both in vitro and in animal models. We evaluated first the acute effect of i.v. glucocorticoids on adiponectin in normal subjects and secondly plasma adiponectin levels in a series of patients with Cushing's syndrome compared with controls. Design and methods: Hydrocortisone (25 mg) was administered i.v. to five healthy volunteers, with blood samples taken at 215, 0, 30, 60, 120 and 180 min. Twenty-one patients with Cush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 39 publications
4
84
2
5
Order By: Relevance
“…The mechanisms underlying social-defeat-induced reduction in circulating adiponectin levels are not yet known. However, studies have shown that glucocorticoid stress hormones inhibit adiponectin gene expression and secretion both in vitro and in vivo (39)(40)(41)(42). It seems reasonable to speculate that social-defeat-induced decrease in plasma adiponectin levels may be attributed to stress-induced glucocorticoid surge.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying social-defeat-induced reduction in circulating adiponectin levels are not yet known. However, studies have shown that glucocorticoid stress hormones inhibit adiponectin gene expression and secretion both in vitro and in vivo (39)(40)(41)(42). It seems reasonable to speculate that social-defeat-induced decrease in plasma adiponectin levels may be attributed to stress-induced glucocorticoid surge.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of excess glucocorticoids on the blood adiponectin levels remain controversial. In human medicine, a study found that patients with Cushing's syndrome had lower adiponectin levels than the controls, which suggests that hypercortisolemia directly affected the adiponectin levels independent of body weight 43. However, another study reported that the serum adiponectin levels in patients with Cushing's syndrome did not differ from those in the control group and they were not changed significantly after hypophysectomy, despite a significant decrease in the body fat mass, insulin resistance, and cortisol 36, 44.…”
Section: Discussionmentioning
confidence: 99%
“…After cessation of the IVGTT, blood glucose, plasma insulin and corticosterone levels returned to normal, but a higher plasma adiponectin and lower resistin levels in CAP rats relative to VEH controls was found at this stage. It might be possible that the transiently different plasma corticosterone levels in CAP and VEH rats contributed to these effects [25,26] but additional or more important factors are not ruled out. While it is unlikely that the changes in adiponectin and resistin levels contributed to the differences in glucose-toinsulin indexes during the preceding IVGTT, they might have a major impact on successive excursions of blood glucose or on the metabolic consequences of these.…”
Section: Discussionmentioning
confidence: 99%